100 great leadership ideas : from successful leaders and managers around the world - Gifford, Jonathan Lewis. 4 0 16; 5 (London : Marshall Cavendish Business, 2010)
Draws from the wisdom of over 130 modern leaders to present one hundred of the most significant leadership ideas, concepts, and practices.
Includes bibliographical references.
Adult.
Keywords: 2 -- 0; 6; Leadership. -- 20; 20; 2